ANALISA KARAKTERISTIK CURAH HUJAN DAN KURVA INTENSITAS DURASI FREKUENSI (IDF) DI PROPINSI LAMPUNG - Susilowati A; Dyah Indriana Kusumastuti (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
This research was done to analyze the characteristic of rainfall that agreed with the short termduration of rainfall data at BMG Maritim Lampung station, BMG Raden Inten II Bandar Lampungstation, Masgar Tegineneng Climatology station and Kotabumi Geophysical station. From theresults of research will be made intensity duration frequency (IDF) curve based on: (1) Analysis offrequency rain distribution of short term rainfall data from each stations. (2) Analysis of rainfallintensity for every rain duration in particular when reuses Van breen intensity method and Hasperder weduwen intensity method then doing calculate approach of rainfall intensity using leastsquare are Talbot, Sherman and Ishiguro formula’s, it means to determine the equality of rainfallintensity to program region. From the result of research could be summarized as follows ;(1) Thedata of rainfall used is short term rainfall data (5, 10, 15, 30, 45, 60, 120 minutes, 3 hours, 6hours and 12 hours) and as annual maximum series, (2) Type of distribution that appropriate withall observation station is Log Pearson Type III Distribution, (3) The rainfall intensity of VanBreen method used Talbot equality, it is used as reference to form IDF curve. The intensityequality was valid only to data of rain in all observation year at every station. (4) The IDF Curveshowed that high rainfall intensity ran in short duration (5) the IDF curve can be used fordetermine planning flood by using rational method.